Fuel cell cogeneration system: a case of technoeconomic analysis - Silveira, J. L.; Gomes, L. A. (Elsevier B.V., 1999)
Fuel Cell is the emerging technology of cogeneration, and has been applied successfully in Japan, U.S.A. and some OECD countries. This system produces electric power by an electrolytic process, in which chemical substances (the most utilized substances are solid oxide, phosphoric acid and molten carbonate) absorb the components H-2 and O-2 of the combustion fuel. This technology allows the recovery of residual heat, available from 200 degrees C up to 1000 degrees C (depending on the electrochemical substance utilized), which can be used for the production of steam, hot or cold water, or hot or cold air, depending on the recuperation equipment used. This article presents some configurations of fuel cell cogeneration cycles and a study of the technical and economic feasibility for the installation of the cogeneration systems utilizing fuel cell, connected to an absorption refrigeration system for st building of the tertiary sector, subject to conditions in Brazil. (C) 1999 Elsevier B.V. Ltd. All rights reserved.